The impact of clouds on the brightness of the night sky. (May 2020) - Ściężor, Tomasz
Highlights: Clouds are the main factor of ecological light pollution. There is a clear linear dependence of the night sky brightness and the cloudiness. There are three groups of light polluted areas connected to the population density. Night sky brightness depends on the clouds genus. Brightness of the night sky depends on the altitude of clouds base. Abstract: Clouds are a kind of atmospheric factor that most effectively scatters the artificial light coming from the ground. Therefore, they have the most significant impact on the brightness of the night sky. The paper analyses the influence of both the level of cloudiness, as well as the genera of clouds and altitude of its base, on amplifying of the light pollution. The impact of cloudiness on the brightness of the night sky in places with different levels of light pollution was researched. Measurements of meteorological elements were used together with clouds genera assessments. The introduction of an innovative method of identifying some genera of clouds on the base of the all-night continuous measurements of the sky's brightness allowed for a similar analysis in the absence of observational data specifying the genera of clouds. A linear correlation between the cloudiness and the brightness of the night sky was found. The determined linear correlation parameters allow for specifying the three types of light-polluted areas, possibly related to the density of population. It was found that among the nine genera of the identified night clouds, the Altocumulus, Cirrocumulus, and Cumulonimbus ones are responsible for this correlation. No dependence of the brightness of the night sky on the clouds' albedo was found. In case of overcast sky, there was a clear relationship between the average altitude of the individual genus of clouds and the brightness of the night sky. Most of the night sky brightness comes from the light scattered on the lowest altitude clouds genera, while the least contribution comes from the light scattered on the high-level clouds. It was also found that at the freezing temperatures, the layer of aerosols forms below the level of the genera Nimbostratus or Stratus. This layer, thickening with the decreasing temperature, additionally scatters the artificial light.